Overview Fitoremediasi Dalam Pengelolaan Tanah Tercemar Kadmium (Cd) - Nasution, Rizki Khoiriah (Universitas Bojonegoro, 2024)
Economic development and anthropogenic activities, such as industry and agriculture, lead to deepening soil pollution by heavy metals. Heavy metal pollution threatens human health through the food chain, air and direct contact. Agricultural soils are often polluted by mining waste residues, pesticides, and sewage disposal, which require immediate attention. Heavy metals such as cadmium (Cd), which cannot be biodegraded, have high toxic potential and adversely affect plant health, growth and food production. Conventional remediation methods, such as physical and chemical, face challenges such as high costs and the risk of secondary pollution. As an alternative, phytoremediation offers an environmentally friendly and low-cost solution by using plants to accumulate and remove heavy metals. This method is effective in reducing Cd pollution in soil. The purpose of the literature review is to compare plants that have effectiveness in cadmium absorption in soil. Based on the review of previous studies, it shows that plants such as Impatiens balsamina L (96%) and Red Cockscomb Celosia plumosa (Voss) Burv (85%) are highly efficient in Cd sorption and suitable for phytoremediation applications. This phytoremediation technology offers an easy and effective way to deal with heavy metal pollution in soil.